Using Computers to Realize Joint Gains in Negotiations: Toward an “Electronic Bargaining Table” - Rangaswamy, Arvind; Shell, G. Richard (Management Science, 1997)
Multiissue negotiations present opportunities for tradeoffs that create gains for one or more parties without causing any party to be worse off. The literature suggests that parties are often unable to identify and capitalize on such trades. We present a Negotiation Support System, called NEGOTIATION ASSISTANT, that enables negotiators to analyze their own preferences and provides a structured negotiation process to help parties move toward optimal trades. The underlying model is based on a multiattribute representation of preferences and communications over a computer network where offers and counteroffers are evaluated according to one's own preferences. The parties can send and receive both formal offers and informal messages. If and when agreement is reached, the computer evaluates the agreement and suggests improvements based on the criteria of Pareto-superiority. In this paper, we motivate the system, present its analytical foundations, discuss its design and development, and provide an experimental assessment of its “value-in-use.” Our results strongly suggest that parties using the system in structured negotiation settings would achieve better outcomes than parties negotiating face to face or over an e-mail messaging facility, other things being equal. For example, only 4 of the 34 dyads (11.1%) negotiating a simulated sales transaction face to face or over e-mail reached an “integrative” settlement, as compared with 29 of the 68 dyads (42.6%) using NEGOTIATION ASSISTANT. Systems such as NEGOTIATION ASSISTANT have the potential to be used in emerging “electronic markets.”